A woven fabric for interconnecting back‐contact solar cells. (6th December 2016) - Borgers, Tom; Govaerts, Jonathan; Voroshazi, Eszter; Jambaldinni, Shruti; O'Sullivan, Barry; Singh, Sukhvinder; Debucquoy, Maarten; Szlufcik, Jozef; Poortmans, Jef
Abstract: This paper reports on a novel and highly innovative technology to interconnect back‐contact cells. First, a background section explains the currently developed interconnection technologies. Then, our novel concept is introduced: interconnection of the cells is achieved with a woven fabric, combining both conductive wires, needed for the interconnection, and insulating wires, crucial to avoid shunting between both polarities at the backside of the cell. Weaving also allows out‐of‐plane stress relief features. In the third section, we explain that our technology combines the advantages of multi‐wire interconnection such as low‐stress and reduced resistive losses with known and low‐cost materials of traditional module assembly. Additional to previous publications, we demonstrate that the technology can be tuned broadly in terms of costs and resistive losses using an optimized interconnection pattern. These resistive loss simulations are also validated with the measured additional resistance in IBC test samples. We also present a preliminary thermal cycling test with promising results. Finally, first functional demonstrators IBC cells are fabricated, disclosing the process flow and initial technology developments. These results clearly demonstrate the proof‐of‐concept of the woven interconnection fabric, and based on electrical characterization we provide suggestions for improvements. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A new approach for interconnecting back‐contact cells is introduced, where an array of wires is floats above the cell metallization because of the use of glass fibres in a woven fabric. The interconnection is realized by solder paste forming a contact between cell metallization and wires, and interruption of these wires at certain locations to provide the appropriate electrical pattern. First simulations towards performance and costs, proof‐of‐concepts and reliability tests are elaborated.